PLUS mobile app: product promotion / Siti Saleha Sudirman - Sudirman, Siti Saleha (Faculty of Art and Design, 2020)
PLUS mobile application is based on PLUS Malaysia Berhad. The application includes a variety of functions to help users of the road plan their journey while they are on the highway, especially during festive season and school holidays.